Effects of Foot Reflexology Integrated with Medical use on Hemoglobin A1c and Ankle Brachial Index in Older Adults with Type 2 Diabetes Mellitus. - Yodsirajinda, Sineenat; Piaseu, Noppawan; Nicharojana, Ladaval Ounprasertpong (The Bangkok Medical Journal, 2016)
OBJECTIVE: To compare hemoglobin A1c (HbA1c) levels and ankle brachial index(ABI) in older adults with type 2 diabetes mellitus (T2DM) between the experimentalgroup and the control group two months after receiving the foot reflexology program, andto compare HbA1c levels and ABI in older adults with T2DM in the experimental groupbefore and two months after receiving the foot reflexology program. MATERIALS AND METHODS: A randomized experimental design with a randomizedcontrolled two-group pretest-posttest design. The purpose of the study was toinvestigate the effects of foot reflexology integrated with medication use on HbA1cand ABI in older adults with T2DM who sought treatment at the diabetes clinic ofManorom Hospital, Manorom District, Chai Nat Province. The study sample consistedof 40 older adults with T2DM who sought treatment at the diabetes clinic who metthe inclusion criteria. The subjects were recruited through random sampling, with 20assigned into the experimental group and the other 20 into the control group. The subjectsin the experimental group received foot reflexology every day for a period of twomonths, while those in the control group did not receive such treatment. All of thesubjects in both groups received pharmacological treatment of diabetes with eitheroral medication or insulin injection as prescribed in the treatment plan based on theirmeasurements with HbA1c used the ARRAY High Performance Liquid Chromatography(HPLC), and ABI level use the doppler ultrasound with handheld doppler probe.Data were analyzed using inferential statistics, Independent t-test and Paired t-test. RESULTS: The results revealed that after receiving foot reflexology, the HbA1c of theexperimental subjects was lower than that of the control subjects (t = 2.76, p = 0.009,SD = 1.37). In addition, their ABI levels in the right leg and left leg were higher thanthose of the control subjects (t = 5.921, p < 0.001, SD = 0.044 and t = 9.155, p = <0.0001, SD = .016 respectively). Also, after receiving foot reflexology, the subjects inthe experimental group had lower HbA1c (t = 10.54, p < 0.001, SD = 0.96) and ABIlevels in their right leg and left leg (t = -8.475, p < 0.001, SD = 0.044 and t = -10.249,p < 0.001, SD = 0.060 respectively).CONCLUSION: Foot reflexology can reduce HbA1c and increase ABI in older adultswith T2DM. It can be implemented as a complementary therapy to control diabetes andreduce severity of complications of diabetic foot in older adults with T2DM.